Debates and developments in ethnographic methodology - Walford, Geoffrey (Amsterdam : JAI, 2002)
What counts as ethnography and what counts as good ethnographic methodology are both highly contested. Volume 6 of this expanding series of books draws together a collection of chapters presenting a diversity of views on some of the debates and developments in ethnographic methodology. It does not try to present a single coherent view but, through its heterogeneity, illustrates the strength and liveliness of debate within this area. The chapters cover central topics such as the challenges to conventional views about validity in ethnographic work, feminist research, comparison within ethnographic research, the public identification of research sites, and the ethics and practice of research involving children. Other chapters deal with relatively newer topics such as the conduct of electronic ethnography, the development of the imagination and emotion within ethnographic writing, and the use of hypertext in the analysis and representation of ethnographic work.
Description based on print version record.
Keywords: Ethnology -- Methodology; Educational anthropology; Philosophy & theory of education; Social & cultural anthropology; Social Science -- Methodology; Education -- Research